Effective Factors on the Acceptance of Information Technology by Academic Librarians of Isfahan Based on TAM - Zahra Jalali (پیاورد سلامت, 2017)
Background and Aim: Functions and services of academic libraries have been affected very much by the entrance and the development of information technology (IT) in university libraries. Since the main mission of academic libraries is advance of educational and research programs of university, the authorities should deploy expertise with technical skills to be able to fulfill their most important job. The aim of this study was to identify factors influencing the adoption of information technology by librarians of governmental academic libraries based on the Technology Acceptance Model (TAM). Materials and Methods: This was a survey research and the tool was a questionnaire based on TAM. The study population consisted of 151 librarians and census method was used. The validity was confirmed by experts in library and information sciences and also IT. Reliability obtained 0.89 using Cronbachchr('39')s alpha. Statistical method was descriptive, inferential and data analysis was done via software SPSS20. Results: Determination coefficient 0.282 shows that TAM is applicable in research population. This means that the applicability of the TAM was relatively appropriate for study about librarians of university libraries. Priorities effects of TAMs variables on the actual use of IT shows the most effective variable are intent to use (0.39), perceived ease of use (0.21), perceived usefulness (0.15) and attitude to use of IT (0.12). Conclusion: Provision of required IT infrastructure and training for effective use should be considered for librarians.  In addition to that, courses of introduction to library information technology should be included in the library and information science curriculum.